Renouveler les connaissances sur les risques liés aux sports de montagne : l’exemple d’un laboratoire collaboratif d’accidentologie - Maud Vanpoulle; Bastien Soulé; Eric Boutroy; Brice Lefèvre (Revue de Géographie Alpine)
The risks associated with the practice of alpine sports are a major concern in mountain environments. Quantifying and explaining the causes of accidents are key to improving knowledge about this sensitive issue. To this end, since 2015, the Laboratory of Vulnerabilities and Innovation in Sport (L-ViS) has been participating in collaborative action research in France involving parties from several spheres: the Petzl Foundation (Petzl is a French climbing and caving equipment company), the online community Camptocamp (aimed at those who practice mountain sports), stakeholders from the public sector (mountain rescue services and the National Observatory of Mountain Safety, SNOSM) and the non-profit sector (sports federations), and professionals (guide organizations). At the end of 2015, this collaborative project resulted in the launch of an online system to collect participatory testimonials on accidents and incidents occurring during the practice of mountain sports: the SERAC database. The development, implementation and growing interest of multiple stakeholders regarding this collaborative approach to sharing experiences mark it as an innovative way to understand and optimize alpine accidentology. Seen through the lens of the sociology of science and technology, the process of social innovation the SERAC database represents is a form of knowledge production that links researchers, communities of alpine sports practitioners and their sporting culture, the alpine environments where they are practiced, and specific safety agencies. This article describes the creation, socialization and evolution of the research project associated with the SERAC database, highlighting the hybrid and uncertain nature of the knowledge produced and how it is inextricably linked with the mountain environment. At its source, the SERAC project has two complementary but also divergent aims: that of collaborative action research to support social innovation, and the production of contextualized knowledge that can ideally be translated into accident prevention recommendations and a better understanding of risky alpine practices.